Beyond tissue biopsy: a diagnostic framework to address tumor heterogeneity in lung cancer - Voigt, Wieland; Manegold, Christian; Pilz, Lothar; Wu, Yi-Long; Müllauer, Leonard; Pirker, Robert; Filipits, Martin; Niklinski, Jacek; Petruzelka, Lubos; Prosch, Helmut (Current opinion in oncology, 2020)
PURPOSE OF REVIEW: The objective of this review is to discuss the strength and limitations of tissue and liquid biopsy and functional imaging to capture spatial and temporal tumor heterogeneity either alone or as part of a diagnostic framework in non-small cell lung cancer (NSCLC). RECENT FINDINGS: NSCLC displays genetic and phenotypic heterogeneity - a detailed knowledge of which is crucial to personalize treatment. Tissue biopsy often lacks spatial and temporal resolution. Thus, NSCLC needs to be characterized by complementary diagnostic methods to resolve heterogeneity. Liquid biopsy offers detection of tumor biomarkers and for example, the classification and monitoring of EGFR mutations in NSCLC. It allows repeated sampling, and therefore, appears promising to address temporal aspects of tumor heterogeneity. Functional imaging methods and emerging image analytic tools, such as radiomics capture temporal and spatial heterogeneity. Further standardization of radiomics is required to allow introduction into clinical routine. SUMMARY: To augment the potential of precision therapy, improved diagnostic characterization of tumors is pivotal. We suggest a comprehensive diagnostic framework combining tissue and liquid biopsy and functional imaging to address the known aspects of spatial and temporal tumor heterogeneity on the example of NSCLC. We envision how this framework might be implemented in clinical practice.
Keywords: genetická heterogenita; biopsie; nádory plic; Genetic Heterogeneity; Biopsy; Lung Neoplasms; Humans; lidé; individualizovaná medicína; Precision Medicine